BK virus and cancer in Uganda. - Newton, R; Ribeiro, T; Alvarez, E; Ziegler, J; Casabonne, D; Carpenter, L; Beral, V; Mbidde, E; Parkin, D; Wabinga, H; Mbulaiteye, S; Jaffe, H; et al. (2006)
As part of an epidemiological study of cancer in Uganda, we investigated the titre of antibodies against BK virus among 821 people with different cancer types and benign tumours. Among study participants, 790 were considered seropositive for anti-BK virus antibodies and all analyses were conducted on transformed data. The mean optical density (a measure of antibody titre) for all patients combined (including the 31 who were considered seronegative) was 1.03 (standard error 0.01), but was 5% higher in women than in men (P=0.05), and 8% higher among HIV seropositive than seronegative people (P=0.002). Otherwise, there were few consistent associations between anti-BK virus antibodies and any social and lifestyle factor investigated. Differences in the mean optical density for each cancer type were estimated using multivariate analysis of variance with adjustment for sex, age group and HIV serostatus, using all other patients as controls. The mean optical density was about 17% lower among those with oral cancer (optical density 0.86, standard error 0.06; P=0.01, based on 30 patients) and about 20% higher among those with prostate cancer (optical density 1.22, standard error 0.09; P=0.01, based on 11 cases) than among all other patients combined. The number of cases of each cancer was too small to exclude the possibility of these findings arising by chance. No other cancer site or type was significantly associated with low, or with high anti-BK virus antibody titres.